Exploring The Need for Reflective Journal as Assessmentas-Learning in A Government LMS: A Study of BPOM Employees - Kurniati, Kiki; Rejekiningsih, Triana; Sumaryati, Sri (Universitas Muhammadiyah Surakarta, 2025)
The advancement of digital learning in government institutions calls for assessment models that go beyond summative testing and foster self-regulated learning. These preliminary needs analysis investigates the perceptions and learning needs of employees at the National Agency of Drug and Food Control (BPOM) regarding the development of a reflective journal as an assessment-as-learning feature within the LMS IDEAS. Using a quantitative approach, the study involved 85 active LMS users who responded to an online questionnaire. The results indicate that while current assessments such as pre- and post-tests are perceived as clear and relevant, they are considered insufficient in promoting key aspects of self-regulated learning- namely self-monitoring, evaluation, and adaptation. Respondents expressed strong needs for additional features such as personalized feedback, structured reflection tools, and mechanisms that connect learning with workplace practices. These findings suggest that integrating a reflective journal with guided prompts and flexible formats into the LMS has the potential to enhance autonomous learning and support continuous professional development among civil servants.